Consumption of psychotropic drugs among adolescents during the COVID-19 pandemic (Research, Society and Development, 2022)
The prescription of drugs for the treatment of psychiatric disorders has been a common and successful approach in recent years. In view of the context of the COVID-19 pandemic, which has had negative impacts on the mental health of individuals exposed to this whole situation of uncertainty, the objective of this research is to analyze the use of psychotropic drugs by adolescents during the COVID-19 pandemic, evidencing or not the increase in psychotropic drugs in this group in a troubled period in human history. The methodology used was the integrative literature review, based on searches for published studies on the subject, between the years 2020 and 2022, in our PubMed and Scielo databases. The descriptors chosen were: “adolescents” (adolescents and youth), psychotropics (psychotropics), “anxiolytics” (anxiolytic), “antidepressants” (antidepressive) and “COVID-19”. To search for articles, the Boolean operators AND and OR were used. The results showed that there was an increase in the use of psychotropic drugs by adolescents, with or without a medical prescription, although it cannot be said that this is a worldwide trend. It is concluded that there is a need to verify the best forms of treatment to minimize the negative impacts of the COVID-19 pandemic on the mental health of adolescents.